2000
DOI: 10.1128/iai.68.10.5546-5551.2000
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens Beta-Toxin Forms Potential-Dependent, Cation-Selective Channels in Lipid Bilayers

Abstract: Recombinant beta-toxin from Clostridium perfringens type C was found to increase the conductance of bilayer lipid membranes (BLMs) by inducing channel activity. The channels exhibited a distribution of conductances within the range of 10 to 380 pS, with the majority of the channels falling into two categories of conductance at 110 and 60 pS. The radii of beta-toxin pores found for the conductance states of 110 and 60 pS were 12.7 and 11.1 Å, respectively. The single channels and the steady-state currents induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
65
2
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 27 publications
12
65
2
8
Order By: Relevance
“…CPB forms ϳ12-Å channels that are selective for monovalent cations (90). The toxin shows specificity for only a few cultured cell lines, possibly due to the limited distribution of a still unidentified receptor.…”
Section: Plasmid-encoded Toxinsmentioning
confidence: 99%
“…CPB forms ϳ12-Å channels that are selective for monovalent cations (90). The toxin shows specificity for only a few cultured cell lines, possibly due to the limited distribution of a still unidentified receptor.…”
Section: Plasmid-encoded Toxinsmentioning
confidence: 99%
“…Moreover, the beta toxin can form a multimeric complex on human umbilical vein endothelial cells, suggesting that it can oligomerize, typical for pore-forming toxins (Steinthorsdottir et al, 2000). Shatursky et al (2000) showed that the beta toxin forms sodium and potassium selective channels in lipid bilayers.…”
Section: Perfringens Virulence Factorsmentioning
confidence: 99%
“…Ασκεί την παθογόνο της δράση σχηματί ζοντας πόρους με ολιγομερισμό της κυτταρικής μεμ βράνης. Οι πόροι αυτοί προκαλούν μεταβολή της δια περατότητας της κυτταρικής μεμβράνης, με αποτέλε σμα την εκροή ιόντων καλίου και την εισροή ιόντων JOURNAL OF THE HELLENIC VETERINARY MEDICAL SOCIETY 2010,61(3) ΠΕΡΙΟΔΙΚΟ ΤΗΣ ΕΛΛΗΝΙΚΗΣ ΚΤΗΝΙΑΤΡΙΚΗΣ ΕΤΑΙΡΕΙΑΣ 2010,61(3) νατρίου, ασβεστίου και χλωρίου, οδηγώντας στη διόγ κωση και τελικά στη λΰση του κυττάρου (Shatursky et al 2000, Nagahama et al 2003. Στον άνθρωπο, τα ενδοθηλιακά κύτταρα φαίνεται να αποτελούν τα κύτ-ταρα-στόχος, χωρίς ωστόσο να εκδηλώνει αιμολυτική δράση (Steinthorsdottir et al 2000).…”
Section: τοξίνη -βunclassified
“…Τέλος, σύμφωνα με τους Shatursky et al (2000), η τοξίνη -β εκδηλώνει δράση κυρίως νευροτοξίνης δρώντας στις προγαγγλιακές ίνες ή σε στοιχεία του αυτόνομου νευρικού συστήματος και λιγότερο δράση κυτταρολυσίνης. Η μεταβολή της διαπερατότητας της κυτταρικής μεμβράνης και η διευκόλυνση της ροής των μονοσθενών ιόντων προκαλούν ταχύτατη και μη αναστρέψιμη εκπόλωση του κυττάρου, με αποτέλεσμα τη βλάβη του νευρώνα (Shatursky et al 2000).…”
Section: τοξίνη -βunclassified
See 1 more Smart Citation